Cardiac Cancers: Classification, Diagnostics and Treatment - Simonavičius, Paulius (Lietuvos chirurgija, 2023)
Although rare, cardiac tumors are a type of surgical pathology that can present itself during clinical practice. Like the majority of neoplasms, these tumors are classified into two groups: primary and secondary or benign and malignant. However, the classification does not determine treatment, but the diagnostic pathway is the same and this pathology does not revolve only around the cardiologist an/or cardiac surgeon for optimal patient outcomes. That is why it is important for doctors of multiple specialties to work on cardiac tumor diagnostics and treatment all together. Aim of this study – to analyze the information about cardiac tumor classification, diagnostics, and treatment. Results of the study. The results clearly show that cardiac tumors are a rare type of pathology and their classification depends on type of tissue the neoplasm originated from. It can either be from one of heart layers (primary tumor) or a metastasis (secondary tumor). It is also important to classify these tumors into benign and malignant because treatment differs drastically. Diagnostic tests that are essential for cardiac tumors are instrumental (heart ultrasound, MRA, CTA) and blood tests (troponins, D-dimers). Treatment varies depending on tumor type however surgery is usually the only option. Treatment of malignant tumors is more complex, involving chemotherapy and/or radiotherapy and outcomes of these neoplasms are generally worse compared to treatment of benign heart tumors.